Towards the Future of New Uzbekistan: Science, Technology, and Education (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
This article explores the strategic importance of science, technology, and education in shaping the future development of New Uzbekistan. It analyzes ongoing national reforms aimed at strengthening scientific research capacity, accelerating technological innovation, and modernizing the education system in accordance with global standards. Special attention is given to digital transformation, innovation ecosystems, and human capital development as key drivers of sustainable economic growth. The study argues that the effective integration of scientific knowledge, advanced technologies, and high-quality education is essential for building a competitive, knowledge-based economy. The article concludes that long-term investment in research, innovation, and education will ensure social stability, economic resilience, and global competitiveness for New Uzbekistan.